2013
DOI: 10.1134/s1062359013080025
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the range of the Siberian roe deer (Capreolus pygargus, Cervidae) and its present distribution in Yakutia

Abstract: Data on the distribution of the Siberian roe deer in Yakutia in the past and at present are presented. The dynamics of the species range in the Holocene is considered. The ways of formation of the new range of Siberian roe deer in this region in the 20th century are analyzed. The structure of the range of this species in different ecological and geographical regions of Yakutia is discussed. Cases of occurrence of the Siberian roe deer in the subarctic zone are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This result may be attributable to mixed samples from historically split populations or to stable populations with large long‐term effective population sizes (Grant & Bowen, ). High nucleotide diversity of Siberian roe deer at the northern periphery of its geographical range in Yakutia (RYA) may belong to the former scenario as it was reported that the population there is a mixture of two subspecies, C. p. pygargus and C. p. tianschanicus (Argunov, ; Boeskorov & Danilkin, ). Co‐occurrence of two subspecies could result in high genetic diversity in a mixed sample.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be attributable to mixed samples from historically split populations or to stable populations with large long‐term effective population sizes (Grant & Bowen, ). High nucleotide diversity of Siberian roe deer at the northern periphery of its geographical range in Yakutia (RYA) may belong to the former scenario as it was reported that the population there is a mixture of two subspecies, C. p. pygargus and C. p. tianschanicus (Argunov, ; Boeskorov & Danilkin, ). Co‐occurrence of two subspecies could result in high genetic diversity in a mixed sample.…”
Section: Discussionmentioning
confidence: 99%
“…Roe deer population in Yakutia, Russia (RYA), were established as a result of natural radiation from the southern parts of geographical range and could originate from both C. p. pygargus and C. p. tianschaniscus [ 43 ]. This assumption complies with the genetic structure of the Yakutian population obtained in this study and is also confirmed by the previous studies using morphology and karyotype [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%